Increased pulmonary and intestinal permeability in Crohn's disease. Issue 5 (May 1992) - Adenis, A; Colombel, J F; Lecouffe, P; Wallaert, B; Hecquet, B; Marchandise, X; Cortot, A
Abstract : We tested the hypothesis that an increased epithelial permeability may affect sites other than the intestine in patients with Crohn's disease by simultaneously evaluating their pulmonary and intestinal permeability. Pulmonary and intestinal permeability were measured by clearance of inhaled technetium-99m diethylene triamine pentacetate (99mTc-DTPA) and by urinary recovery of chromium-51 ethylene diamine tetracetate respectively in 22 patients with Crohn's disease. The half time clearance of 99mTc-DTPA from lung to blood (t1/2LB) was decreased–that is pulmonary permeability increased–in the whole group of patients with Crohn's disease as compared with 13 controls (median 45.5 minutes (8-160) v 85 minutes (34-130) (p less than 0.003)). When analysed separately only patients with active Crohn's disease (n = 15) had a decreased t1/2 lung to blood v controls (42 minutes (8-160) v 85 minutes (34-130) (p less than 0.0025)). Among patients with active Crohn's disease, six were studied again when their disease was quiescent and their t1/2 lung to blood did not differ significantly. The intestinal permeability was increased in the whole group of Crohn's disease patients as compared with 15 controls (5.25% (1.2-24) v 1.7% (0.65-5.75) (p less than 0.0002)). When analysed separately both patients with active and inactive Crohn's disease had increased intestinal permeability v controls (8.1% (1.6-24) and 3.5% (1.2.9.2) v 1.7% (0.65-5.75)) (p less than 0.0001, p = 0.05 respectively). Six patients with active Crohn's disease were studied again when their disease was quiescent and their intestinal permeability decreased significantly p less than 0.04). Pulmonary permeability was increased in patients with Crohn's disease but was not greatly influenced by Crohn's disease activity as opposed to intestinal permeability. The mechanism of this increase is unknown, but may be related in some patients to the presence of an alveolitis.